Mental Health of Healthcare Professionals in the Conflict Zone of Syam : an Analysis of Burnout and Secondary Trauma - Nurzahara Sihombing; M. Agung Rahmadi; Helsa Nasution; Luthfiah Mawar (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
This study investigates the profound impact of the protracted humanitarian crisis in the conflict zone of Syam on the mental health of healthcare professionals, employing a systematic meta-analytical approach across 47 independent studies (N = 12,487) published between 2011 and 2023. The findings reveal an alarmingly high prevalence of burnout, reaching 78.3% (95% CI [75.2–81.4]), with emotional exhaustion recorded as the most dominant dimension (M = 3.89; SD = 0.76). Additionally, secondary trauma was identified in 65.7% of all respondents (95% CI [62.4–69.0]), with the primary symptoms manifesting as post-traumatic stress disorder (PTSD) at 44.2% and depression at 39.8%. Meta-regression analysis demonstrated that the duration of exposure to conflict (β = 0.42; p < 0.001) and the intensity of workload (β = 0.38; p < 0.001) served as significant predictors of burnout. Meanwhile, the lack of psychosocial support (OR = 2.34; 95% CI [1.89–2.79]) and critical resource scarcity (OR = 1.98; 95% CI [1.65–2.31]) were strongly correlated with the emergence of secondary trauma among healthcare professionals. Furthermore, diverging from the more individualistic frameworks employed in the studies of Bdaiwi et al. (2020) and Bou-Karroum et al. (2020), this research explores the intricate entanglement of organizational and situational determinants that concurrently shape the mental health landscape of medical personnel operating in the Syam conflict zone. Moreover, the study's original contribution lies in identifying resilience adaptation patterns observed in 34.2% of participants, revealing that endurance capacity was cultivated through collective coping strategies and close peer support. According to the researchers, this study offers a new lens for designing community-based psychological interventions that are both sustainable and contextually grounded for healthcare providers affected by the protracted armed conflict in Syam.